Determination of Benzene, Toluene, Ethylbenzene and Xylenes (BTEX) in Produced Water by Solid Phase Microextraction with Gas Chromatography Flame Ionization Detector (GC-FID) - Eljawashi, Salem A.S. Omar (المؤتمر العلمي الثاني لعلوم البيئة، 2015م, 2015)
During the production of crude oil and gas, large amounts of produced water are generated. These waters have to be analyzed with relation to the chemical composition to figure out the environmental impact of its discharge. Therefore, a study was carried out to evaluate concentration of the BTEX (benzene, toluene, ethylbenzene and xylenes), in produced water samples taken from production facilities and the disposal pit at the oilfield, Libya. SPME with Gas Chromatography Flame Ionization Detector (GC-FID) methods was optimized to determine the target compounds. The results showed that concentrations of the target compounds in the produced water samples ranged from 0.13 to 1.86 ppm. In addition, BTEX values are much higher, (1.86 and 1.70 mg/l), at storage tank outlet (TA,) and discharged stream (pump) respectively, where the produced water is in the earlier steps, before discharging to the pits. In the pit samples (Spt1, Spt2, Spt3 and Spt4) the BTEX values range between 0.11 to 0.22 mg/l. In general, produced water sample taking from the disposal pit contained lower BTEX concentrations than those from the production facilities.
Keywords: GC-FID; Produced Water; Solid Phase